Mutual Relationship Between Upper Extremity Function and Core Muscle Endurance in Patients with Multiple Sclerosis - ÖZKUL, Çağla; GÜÇLÜ GÜNDÜZ, Arzu; ESMER, Murat; YILDIRIM, Muhammed Şeref; ELDEMİR, Kader; İRKEÇ, Ceyla (Clinical and experimental health sciences (Online), 2021)
Objective: This study aimed to determine the relationship between upper extremity function and core muscle endurance in patients with multiple sclerosis (PwMS). Methods: Twenty-two PwMS and 20 healthy controls (HC) were included in this retrospective cross-sectional study. The upper extremity function was assessed by the Nine Hole Peg Test (NHPT). In addition, the core muscle endurance was assessed by the side bridge test, trunk flexor endurance test, trunk extensor test, and prone bridge test. Results: Upper extremity function and core muscle endurance (except extensor endurance) in PwMS were lower compared to HC (p<0.05). In addition, the results of correlation analyses in PwMS showed that both sides’ upper extremity functions were related to EDSS, and trunk flexor endurance (p<0.05). Moreover, the right-upper extremity function was related to the right side bridge endurance test performance while the left-upper extremity function was related to left side bridge endurance test performance and disease duration (p<0.05). Conclusion: These results demonstrated the mutual relationship between upper extremity function and core muscle endurance in PwMS. Therefore, the core stabilization training may improve both the core muscle endurance and upper extremity function in PwMS.